Analisis Komparatif Kurikulum Matematika SMP di Indonesia dan Australia: Implikasi untuk Penguatan Pembelajaran di Indonesia - Ferra Fijantari; Nur Robiah Nofikusumawati Peni (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Mathematics learning in junior high schools plays an important role in shaping logical thinking skills and problem-solving skills, but the implementation of the Independent Curriculum in Indonesia still faces various challenges such as limited teacher training and educational infrastructure. Therefore, a comparative study of the Australian curriculum which is more structured, contextual, and competency-based is needed to identify best practices that can be adopted to strengthen the quality of the junior high school mathematics curriculum in Indonesia. This study uses a descriptive-comparative qualitative approach by analyzing junior high school mathematics curriculum documents in Indonesia and Australia in depth through literature and documentation studies, in order to compare the content, structure, learning approaches, and assessments, with data validation carried out through source triangulation and expert discussions. This study concludes that the junior high school mathematics curriculum in Indonesia and Australia has significant differences in structure, learning approaches, content, and assessment systems. Indonesia stands out in flexibility and authentic assessment, while Australia excels in a systematic curriculum structure and integration of proficiency strands. By adopting best practices from Australia and strengthening training and infrastructure, Indonesia has the opportunity to develop a more adaptive, quality, and globally relevant curriculum.